2019
DOI: 10.3390/genes10060437
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Duffy Phenotypes among Plasmodium vivax Infections in Sudan

Abstract: Negative Duffy expression on the surface of human red blood cells was believed to be a barrier for Plasmodium vivax infection in most Africans. However, P. vivax has been demonstrated to infect Duffy-negative individuals in several Central and East African countries. In this study, we investigated the distribution of Duffy blood group phenotypes with regard to P. vivax infection and parasitemia in Sudan. Out of 992 microscopic-positive malaria samples, 190 were identified as P. vivax positive infections. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 25 publications
3
32
2
1
Order By: Relevance
“…In New Halfa, despite a smaller sample size, 7.5% (7/93) of the febrile patients was P. vivax-positive and Duffy-negatives accounted for 14.3% (1/7) of these infections (Table 2). Across the country, there has been an increase in P. vivax detection and reports in recent years (Albsheer et al, 2019) and our findings indicated that the infection rate in Duffy-negative individuals varies among study sites.…”
Section: Contrasting Proportion Of Duffy-negatives and P Vivax Prevalencesupporting
confidence: 52%
See 1 more Smart Citation
“…In New Halfa, despite a smaller sample size, 7.5% (7/93) of the febrile patients was P. vivax-positive and Duffy-negatives accounted for 14.3% (1/7) of these infections (Table 2). Across the country, there has been an increase in P. vivax detection and reports in recent years (Albsheer et al, 2019) and our findings indicated that the infection rate in Duffy-negative individuals varies among study sites.…”
Section: Contrasting Proportion Of Duffy-negatives and P Vivax Prevalencesupporting
confidence: 52%
“…* Duffy-§ Conventional PCR of genes PvCOI and PvDBP 1. 2 Pf-Pv co-infections; 2 Duffy-Ag available only among Plasmodium spp pos;…”
mentioning
confidence: 99%
“…Study quality was assessed using the JBI Critical Appraisal Tool (Table S2 ). Eighteen studies 18 , 19 , 21 , 23 , 25 29 , 32 , 34 39 , 41 , 42 were high-quality, while nine 17 , 20 , 22 , 24 , 30 , 31 , 33 , 40 , 43 were of moderate quality.…”
Section: Resultsmentioning
confidence: 98%
“…Three studies 20 , 21 , 31 were conducted in South America (2/27, 7.4%) and Asia (1/27, 3.7%). Of the 24 African studies, six were conducted in East Africa (Ethiopia 28 , 43 , Madagascar 25 , 29 , Kenya 40 , and Ethiopia 41 ), seven in Mid Africa (Democratic Republic of Congo 19 , Cameroon 22 , 23 , 32 , 33 , 39 , Angola, and Equatorial Guinea 30 ), seven in West Africa (Mauritania 24 , 42 , Nigeria 36 , 37 , Senegal 34 , Mali 35 , and Benin 38 ), two in North Africa (Sudan 17 , 18 ), one in North and East Africa (Ethiopia and Sudan 26 ), and one in Ethiopia/Botswana/Sudan 27 . Twenty-two articles were cross-sectional studies (22/27, 81.5%), two were case-controls 12 , 40 , and one was a cohort study 35 .…”
Section: Resultsmentioning
confidence: 99%
“…In Sudan, most cases of malaria are caused by P. falciparum but in recent years there has been an increase in P. vivax detection and reports [33]. The proportion of Duffy-negative was 20% (77/384) among febrile patients (Figure 1).…”
Section: Resultsmentioning
confidence: 99%